La protección internacional de la objeción de conciencia: análisis comparado entre sistemas de derechos humanos y perspectivas en el sistema interamericano (2016)
In this article, the recognition of conscientious objection in three international systems for the protection of human rights is analyzed: the Inter-American system, the European system and the United Nations system. The comparative system which is adopted allows for notifications as to common developments, the failings and some tensions which have been confronted by international organs in controversial cases. From this analysis are drawn some lessons which may serve for the guardianship of this law in the Inter- American system.